Electrodeposition of Cu2O Particles by Using Electrolyte Solution Containing Glucopone as Surfactant - Dahyunir Dahlan (Jurusan Fisika FMIPA Universitas Andalas, 2009)
Copper oxide particles were electrodeposited onto indium tin oxide (ITO) coated glass substrates. Electrodeposition was carried out in the electrolyte containing cupric sulphate, boric acid and glucopone. Both continuous and pulse currents methods were used in the process with platinum electrode, saturated calomel electrode (SCE) and ITO electrode as the counter, reference and working electrode respectively. The deposited particles were characterized by X-ray diffraction (XRD) and scanning electron microscopy (SEM). It was found that, using continuous current deposition, the deposited particles were mixture of Cu2O and CuO particles. By adding glucopone in the electrolyte, particles with spherical shapes were produced. Electrodeposition by using pulse current, uniform cubical shaped Cu2O particles were produced